Revision of the Tetragona clavipes (Fabricius, 1804) species-group (Hymenoptera: Apidae: Meliponini) - Nogueira, David Silva; de Oliveira, Favízia Freitas; de Oliveira, Marcio Luiz (Zootaxa, 2022)
The Neotropical bee genus Tetragona Lepeletier & Serville, 1828 is characterized among stingless bees by having a yellow pigmented maculation on body, especially on the clypeus, lower region of the paraocular area and mesosome, velvety genal area, a long and slender mesotibial spur and a glabrous propodeal triangle. The T. clavipes species-group is mainly characterized by having workers with elongated setae on T6, with about 2x the length of setae on T5 and hyaline wings. This group is composed of five species, two of which are described here as new: T. clavipes (Fabricius, 1804), T. perangulata (Cockerell, 1917), T. quadrangula (Lepeletier, 1936), T. mourei sp. nov. and T. korotaii sp. nov.). In this study, we synonymize T. dissecta Moure, 2000 and T. elongata Lepeletier & Serville, 1828 under T. clavipes and we provide an identification key for the workers to the species in T. clavipes species-group.